Ethical aspects of the concept of brain death - A. V. Pinchuk; M. G. Minina; V. L. Vinogradov (Трансплантология (Москва))
The authors attempt to summarize views of leading russian experts in bioethics and medical deontology on the moral and ethical issues related to the development of the concept of brain death and its application in modern medicine. A variety of ethical issues associated with the use of the concept of "brain death" in organ donation and clinical transplantation is noted. The official attitude of representatives of the world's major faiths to the problems of brain death and organ transplantation is reflected. Authors express their own attitude to the issues discussed, as professionals facing daily with challenges of brain death in their own clinical practice.